Status of helicobacter pylori infection and its impact on peptic ulcer disease in high-altitude in Karnali Province - Subedi, Dharma Datta; Giri, Rajendra Mani; Bam, Niraj (Janaki Medical College Journal of Medical Science, 2026)
Background & Objectives: Helicobacter pylori infection is a major contributor to acid peptic disease (APD) and peptic ulcer disease (PUD) worldwide. However, its prevalence and clinical impact in high-altitude populations remain underexplored. This study assessed the status of H. pylori infection and its association with peptic ulcer disease among dyspeptic patients at Karnali Academy of Health Sciences (KAHS). Materials and Methods: A cross-sectional observational study was conducted at KAHS in Jumla, Nepal (altitude 2,500–3,500 m) over one year (2078/08/01–2079/08/30 BS). A total of 143 adult patients aged 15–75 years with dyspepsia or suspected APD attending the OPD were enrolled using complete enumeration. Patients with prior APD treatment, proton pump inhibitor use, or severe comorbidities were excluded. H. pylori infection was diagnosed by blood titer, stool antigen test, or endoscopic biopsy, while peptic ulcers were clinically suspected and confirmed by endoscopy. Socio-demographic data were collected using a structured questionnaire and analysed with descriptive statistics and Chi-square test. Results: Among 143 participants, 80 (56%) were males and 63 (44%) females, with a mean age of 45 years (15–75 years). H. pylori infection was detected in 124 (86.7%) cases: blood titer 39.9%, stool antigen 32.2%, and biopsy 14.7%; 13.3% tested negative. Age-wise distribution showed significant variation in detection methods (χ² = 63.154, p = 0.000). Younger patients (15–30 years) were mainly positive by serology, whereas middle-aged groups showed more diverse diagnostic patterns including stool antigen and biopsy. Conclusions: There was a high prevalence of H. pylori infection among dyspeptic patients in high-altitude regions. Age significantly influences detection methods and possibly disease severity, highlighting the need for context-specific diagnostic strategies and targeted management.